Hirschmann Mobility Among Academics of Highly Ranked EU Research Universities - Edward Bergman (European Regional Science Association (ERSA), 2011)
European universities have lost–and partially regained–key research academics to North American and other attractive university systems. EU efforts to reverse the cycle revolve around the establishment of an attractive European Research Area, within which future academic mobility–and commercial knowledge transmission–might be confined. This paper draws upon a survey of 1800 academics in 200 of Europe's most research-intensive universities to understand the principal reasons that underlie contemporary academic mobility. Mobility is conceptualised in Hirschmann terms as 'exit' from an inadequately performing university, rather than remaining 'loyal' to its existing regime or staying to exercise 'voice' in bringing about necessary improvements. The results from logit modeling of choices and options indicate clearly that academics who evidence either 'loyalty' or 'voice' are significantly less likely to be mobile. Moreover, those who are mobile refuse to restrict possible destinations to the ERA if they value better material conditions or better quality of colleagues, students or university reputation.
Keywords: 330